Karakteristik Tanah pada Kawasan Sawah Lebar Baru Kota Bengkulu dan Aplikasinya dalam Perancangan Geoteknik - Rifqi, Fianco Fakhri; Mase, Lindung Zalbuin; Supriani, Fepy; Misliniyati , Rena; Hardiansyah (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
Soil is an essential and indispensable material in civil engineering and building design, affecting various construction works. The primary function of soil is to support the construction load built on it, so the soil must be able to carry the load. Each type of soil has different characteristics, so it requires special handling, both physically and mechanically. This research aims to determine the soil's physical and mechanical properties and its application using the finite element method in the Sawah Lebar Baru area, Bengkulu City. The Sawah Lebar Baru area is currently developing a new residential area. Based on the tests conducted, the soil in the area is classified as silt with high plasticity (MH). The tests include physical tests such as moisture content, volume weight, specific gravity, grain size analysis, and Atterberg limits, as well as mechanical tests such as free compressive strength test, consolidation test, and direct shear test. The results of this study provide information on the type, characteristics, physical and mechanical properties of soil, as well as its application in geotechnical design. The foundation design test results showed that the maximum vertical load was 32,900 kN/m², and the safety factor value was 3.047 for the 0.5 m depth variation. The maximum vertical load value in the foundation with a depth variation of 0.75 m is 67,500 kN/m², and the most significant safety factor value is 5.909. For the depth variation of 1 m, the maximum vertical load value is 118,050 kN/m², and the safe factor value is 9.864.